Evaporative cooling system for electric vehicles battery pack - Khalid, A. Hilmi; Rahman, Mohammed Ataur; Hawlader, Mohammad Nurul Alam (2013)
One of the biggest obstacles faced by the EVs development is how to maintain battery temperature during operation in the appropriate level to ensure better performance and prolong life expectancy. At times of momentary peak load, battery pack needs to generate a high output within a very short time to meet the power demand of the car. Li-ion batteries can be used efficiently only within a specific temperature range: 20oC to 40oC during the operation. Over the years, many attempts have been made to maintain desired operating temperature range using air / liquid cooling. The dissipation of heat from a surface when cooled with air is rather slow due to low convective heat transfer coefficient. This paper includes the simulation study of three different mediums of cooling: air, liquid and evaporative used for battery cooling purposes. Normally, the two-phase mixture in evaporative cooling will have a very high convective heat transfer coefficient and the removal of heat from the battery pack will be more efficient. Also, during the heat transfer process, the coolant temperature remains fairly constant as it goes through a phase change making the heat dissipation process even faster.